Experimental study on mixed convection heat transfer for thermally developing flow in horizontal ducts with radiation effects - Ganesan, Rajamohan; Narayanaswamy, Ramesh; Gorin, Alexander; Perumal, Kumar (American Society of Mechanical Engineers, 2011)
This research focuses on the interaction of surface radiation with laminar mixed convection heat transfer for thermally developing airflow in horizontal ducts. The duct cross section is made of two differentially heated isothermal vertical walls and two adiabatic horizontal walls. In a series of experiments, the Reynolds number is varied from about Re = 800 to Re = 1200, for two aspect ratios of the duct cross section. The hot wall temperature ranges from 27°C to 100°C, and the emissivity of internal walls are 0.05 and 0.85. The total heat transfer from the hot wall to the cold wall of the duct depends on the mixed convection and also on the surface radiation heat transfer that takes place within the duct. Therefore, it is important that the effects of surface radiation must be properly understood, and accounted for, in the design and analysis of flow and heat transfer through ducts. The results presented here show the effect of surface radiation and mixed convection on the total heat transfer rate within the duct. The flow field within the duct is also made visible by a suitable smoke flow visualization method.